(untitled) (Bangladesh Journal of Pharmacology, 2012)
Hypericum species have been used in traditional medicine in Turkey for thousands of years. In order to determine the cytogenetic effects of Hypericum heterophyllum, human lymphocytes were incubated with the aqueous extracts. Mitotic index frequencies and replication index values were increased with increasing extract concentrations of H. heterophyllum. The results indicate the cytotoxic effects as well as proliferative effects and suggest that the extracts of the compounds exhibit cytotoxic properties as well as mitotic and proliferative properties.